STUDI ELEKTROKIMIA POLIANILIN KOMPOSIT ELEKTRODA PASTA KARBON - , Suriyanti (Jurnal Biofisika, 2013)
Polyaniline  is  widely  used  as  a  material  for  manufacturing  electrodes  such  as biosensor,  biofuel  cell,  and  supercapacitor  application  in  nanocomposite  forms.  In this study, polyaniline has been synthesized in emeraldyne salt forms by  interfacial polymerization  method  and  synthesized  nanocomposite  electrode  of  polyanilinecarbon paste. The polyaniline morphology was characterized by X  -  Ray Diffraction (XRD ) , Scanning Electron Microscopy ( SEM ), Transmission Electron Microscope (TEM)  and  Fourier  Transform  Infrared  (FTIR).  In  XRD  pattern  showed crystal type was  polyaniline  nanofiber  semicrystalline.  The  SEM  image  showed  polyaniline morphology  which  nanoparticle  formed.  The  TEM  result  estabilished  nano-size indicated  by  diameter  size  about  60 -80  nm,  FTIR  result  showed  that  polyaniline which synthesized was conductive polyaniline forms or called emeraldine salt (ES). Electrochemical  studies  showed  that  nanocomposite electrode of polyaniline-carbon paste  be  able  to  increased  the  ion  transfer  efficiency  in  the  composite  electrode. Voltammograms  of  nanocomposite  electrode  of  polyaniline-carbon  paste  seen  at  a potential  0,5V  aniline  oxidation  peaks  and  reduction  peaks  seen  at  -0.1  V  Both  of these curves peaks (oxidation and reduction was not observed clearly).